Transplanted Poesis (Duke University Press, 2025)
The ocean between California and Asia, as well as the world oceans that constitute much of this blue-green Earth credibly troped as Planet Ocean, are the biomorphic and atmospheric elements that sustain and nourish us materially and aesthetically as a daily fact—indeed, as a moment-to-moment reckoning. At times the Pacific in this study functions as an oceanic synecdoche of parts for whole, but at other times oceans from the Indian and Arctic to the Atlantic are touched on as connected to this indeterminate circumference of what is posited and troped as ocean becoming Oceania. Worlding ecopoetics would reframe sites toward reflecting and refracting an innovative poetics of transregional worlding and translocal solidarity. If capital and its aligned forces go on deworlding the everyday world as such, we can link worlding to a reworlding dynamic across Oceania as tied to dwelling responsibly in place and region day by day.